MENINGKATKAN HASIL BELAJARA SISWA MELALUI PEMBELAJARAN BERBASIS AI DAN PENDEKATAN KONSTRUKTISME PADA KONSEP BAKTERI: Indonesia - Gilang Medal Pangrestu; Ilham; Dicky Kurnia; Mohammad Alfarobi (STKIP Subang, 2025)
This study aims to improve students’ learning outcomes on the topic of Bacteria through the application of Artificial Intelligence (AI)–based learning combined with a constructivist approach. The research employed a quasi-experimental method using a One Group Pretest–Posttest Design. The participants were 30 tenth-grade students from SMA Negeri 1 Cibinong Kabupaten Cianjur during the second semester of the 2024/2025 academic year, selected through purposive sampling based on technology readiness. Data were collected using pretest and posttest assessments to measure changes in students’ understanding after the learning intervention. The data were analyzed using gain scores to determine the effectiveness of the AI-based learning model. The findings indicate a significant improvement in students’ learning outcomes following the intervention. These results show that AI-based learning supported by constructivist principles is effective in helping students build conceptual understanding and enhance their academic achievement on the topic of Bacteria.